2011
DOI: 10.2484/rcr.v6i4.515
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory pseudotumor of the colon

Abstract: Inflammatory pseudotumor refers to a nonmalignant or low-grade neoplastic lesion characterized by the presence of spindle-cell proliferation with abundant inflammatory cells. Lung and orbit are the most frequent sites of occurrence, but the lesions may originate in nearly every site in the body, including the abdomen. We present a rare and interesting case of inflammatory pseudotumor of the colon in a 21-year-old male who presented to the emergency room with abdominal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 10 publications
(12 reference statements)
0
15
0
Order By: Relevance
“…The primary tumor is usually found as an isolated nodular lesion in the lungs, abdomen or retroperitoneum in adults [3,4] and intraabdominally in the mesentery and omentum in children [6]. They rarely occur in the genitourinary tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary tumor is usually found as an isolated nodular lesion in the lungs, abdomen or retroperitoneum in adults [3,4] and intraabdominally in the mesentery and omentum in children [6]. They rarely occur in the genitourinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal and retroperitoneal IMTs, by comparison, are usually larger and more aggressive and show high local recurrence rates [4]. In rare cases, IMTs have been found in the bladder, and some authors have suggested that these tumors are sufficiently different from other IMTs that they should be considered a special category [5].…”
Section: Introductionmentioning
confidence: 99%
“…This case report complies with the SCARE guidelines and has been reported in line with the SCARE checklist [1] . Inflammatory pseudo-tumours (IPTs) are rare mesenchymal masses that occur in <0.0001% of the population [2] , [3] , [4] . First described as IPTs in 1954 by Uniker and Iversion [4] , these tumours are benign lesions associated with non-specific inflammatory cellular infiltration with spindle-cell proliferation and are often reactive, infective, or immunological in nature [5] .…”
Section: Introductionmentioning
confidence: 99%
“…First described as IPTs in 1954 by Uniker and Iversion [4] , these tumours are benign lesions associated with non-specific inflammatory cellular infiltration with spindle-cell proliferation and are often reactive, infective, or immunological in nature [5] . They have been described predominantly in the lungs to date; however, they may occur in any anatomical location, mostly in children and young adults [2] , [3] , [4] . Alimentary tract IPTs were first described in the stomach; however, they remain exceedingly rare, particularly in the colon, where their aetiology remains unclear [2] , [3] , [6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation